무심천 인근 상대리 수막재배지에서 지하수 사용 후 배출되는 최종 배수로 물의 수질 특성 - 문상호(Sang-Ho Moon); 김용철(Yongcheol Kim); 황 정(Jeong Hwang) (자원환경지질, 2015)
The Sangdae-ri riverside around Musimcheon stream, flowing through Gadeok-myon of Cheongju City, is one of the representative strawberry fields employing water curtain cultivation (WCC) in Korea. In this area, annual groundwater use for WCC has been calculated by a few methods. On the assumption that all the water flowing through the final ditch may be mostly composed of groundwater, the discharge rate in it can be used as a good proxy for assessing the groundwater use. However, in the study area, the final ditch was set up in an unpaved state near and parallel to Musimcheon stream. Under such circumstances, the drainwater is likely to be influenced by infiltration and/or inflow of nearby stream. Hence, we examined whether or not stream water has influenced water flowing out through the final ditch in respect of ion concentrations or field parameters such as T, pH and electrical conductivity (EC) values. The period of measuring field parameters and sample collection was from February 2012 through February 2015. The drainwater in the final ditch did not show the average quality of groundwater, but similar quality of stream water in respect of pH, EC, ion contents and water type. From this, it is suggested that measuring the flow rate of the final ditch should not be directly used for assessing groundwater use in the study area. In addition, because of its sensitivity to ambient temperature, water temperature proved not to be appropriate for estimating the interaction between ditch and stream. For accuracy, additional methods will be needed to calculate mixing ratios between stream and ground water within drainage system. 우리나라의 대표적 딸기 수막재배지 중 하나인 청주시 가덕면 상대리 일대에서는 수막재배용 지하수 이용량이 몇가지 방법으로 산정된 바 있다. 이러한 지하수 이용량 산정 방법 중에는 수막재배 사용 후 배출되는 배수로의 유량을 근거로 하는 것이 있으며, 이러한 방법은 배수로의 물이 모두 사용 후 배출되는 지하수로만 구성되어 있다는 가정 하에 적용된다. 연구지역에서 지하수가 사용된 후 무심천으로 유출되기 직전의 최종 배수로는 비포장 상태이며 하천 가까이에 나란히 개설되어 있다. 이러한 상황에서는 배수로의 물이 인근 하천수의 침투 유입에 의한 영향을 받을 가능성이 있다. 이 연구는 상대리 지역에서와 유사한 하천과 배수로의 구조 및 형태를 가지는 경우에, 최종 배수로의 배출수가 수질의 관점에서 하천수의 영향을 받고 있는지의 여부를 검토해 보았다. 고려된 수질 요소는 현장 수온과 pH, EC 값, 실내 분석에 의한 이온 함량과 수질 유형이며, 현장 측정 및 시료 채취 기간은 2012년 2월부터 2015년 2월까지이다. 검토 결과, 배출수는 지하수의 평균 수질을 반영하지 않으며, 오히려 하천수의 수질을 많이 반영하는 것으로 나타났다. 이로 보아, 연구지역에서와 같이 배수로가 인근 하천 가까이에서 비포장 상태를 유지하는 경우에는, 배출수의 유량 측정을 지하수 이용량 산정에 직접적으로 이용하는 데에 많은 주의가 필요한 것으로 판단되었다. 이 연구에서 배출수의 수온은 주변 대기 온도에 매우 민감하게 반응하여 변하기 때문에, 하천수의 영향을 정량적으로 판단하기는 부적절한 요소인 것으로 나타났다. 향후 배출수 내 지하수와 하천수의 혼합 비율을 정량적으로 산정하는 연구가 병행되어야 할 것으로 사료된다.